2017
DOI: 10.1620/tjem.243.107
|View full text |Cite
|
Sign up to set email alerts
|

Vasohibin-1 Is a Poor Prognostic Factor of Ovarian Carcinoma

Abstract: Vasohibin-1 (VASH1) is an identified negative feedback inhibitor of angiogenesis induced by vascular endothelial growth factor (VEGF) in vascular endothelial cells (ECs). Expression of VASH1 has been reported not only in ECs of normal tissue, but also in ECs surrounding malignant tumors. In malignant tumors, VASH1 is also gaining attention as a prognosis prediction marker. The aim of this study is to investigate the correlation between VASH1 expression and vascular-related factors and various clinicopathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The VASH family, which includes vasohibin-1 (VASH1) and vasohibin-2 (VASH2), is a novel family of angiogenesis regulators [ 84 ] that act as tubulin-specific CCPs [ 40 , 45 ]. According to their role in angiogenesis, high expression of VASH1 and VASH2 was associated with poor clinical outcomes in gastric, ovarian, and esophageal squamous carcinoma patients [ 85 , 86 , 87 , 88 ]. Despite this, the relationship between the tubulin CCP activity of VASH1/2 and cancer progression or drug sensitivity is still a matter of debate.…”
Section: The Tubulin Code and Its Associated Enzymes In Cancermentioning
confidence: 99%
“…The VASH family, which includes vasohibin-1 (VASH1) and vasohibin-2 (VASH2), is a novel family of angiogenesis regulators [ 84 ] that act as tubulin-specific CCPs [ 40 , 45 ]. According to their role in angiogenesis, high expression of VASH1 and VASH2 was associated with poor clinical outcomes in gastric, ovarian, and esophageal squamous carcinoma patients [ 85 , 86 , 87 , 88 ]. Despite this, the relationship between the tubulin CCP activity of VASH1/2 and cancer progression or drug sensitivity is still a matter of debate.…”
Section: The Tubulin Code and Its Associated Enzymes In Cancermentioning
confidence: 99%
“…Vasohibin expression and its impact on prognosis have been studied in patients with breast, endometrial, cervical, liver, pancreatic, colorectal, non-small cell lung, renal cell, head and neck squamous cell, esophageal squamous cell, upper urothelial, prostate, and ovarian cancers. All of these studies found that vasohibin expression (VASH1 alone, VASH2 alone, or both VASH1 and VASH2) was associated with poor prognosis, suggesting its utility as a new biomarker [18,19,[22][23][24][25][26][27][28][29][30][31][32][33][34]. In particular, the association between VASH2 expression and tumor growth has been studied in patients with pancreatic, esophageal squamous cell, and ovarian cancers [19,22,29].…”
Section: Discussionmentioning
confidence: 99%
“…studies were identified as meeting our inclusion criteria [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], whose detailed information was shown in Table 2. The VASH1 relatively-low expression group (1225 individuals; 52.8%) was regarded as the control group.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%